Anti-HIV Therapy: Current and Future Directions - Agrawal, Lokesh; Lu, Xihua; Jin, Qingwen; Alkhatib, Ghalib (Current Pharmaceutical Design, 2006)
Although combinations of drugs that target the HIV reverse transcriptase and protease enzymes have clearly revolutionized the treatment of HIV/AIDS, problems with these agents, such as viral escape mutants, persistence of viral reservoirs, poor patient compliance due to complicated regimens, and toxic side effects, have emphasized the need for development of new drugs with novel mechanisms of action, as well as an HIV vaccine. Recently two new classes of drugs have been identified that interfere with the membrane fusion reaction required for HIV entry of target cells. Two such agents, T-20 (enfuvirtide) and T-1249, which have been approved by the Food and Drug Administration (FDA), block the action of the fusogenic envelope glycoprotein gp41. Others target the HIV coreceptors CCR5 and CXCR4, and are now in clinical trials. Also under development are novel agents that target the HIV integrase and HIV regulatory gene products as well as immunomodulators such as IL-12 and IL-2. This article will focus on these and other novel approaches to HIV therapeutics.
Keywords: CCR5